Fire and lichen dynamics in the Taiga Shield of the Northwest Territories and implications for barren‐ground caribou winter forage. (2nd May 2019) - Lewis, Kathy J.; Johnson, Chris J.; Karim, MD. Nayeem
Abstract: Questions: Fire is the main disturbance agent in boreal forests and has profound effects on vegetation composition and structure, including terrestrial lichens that provide critical winter forage for barren‐ground caribou. What is the influence of fire on forest structure and the distribution and species assemblage of forage lichens? What is the current or potential effect of climate change on forage lichen in the boreal forest? Location: High Boreal, Low Subarctic, and High Subarctic ecoregions of the Taiga Shield Ecozone in the Northwest Territories, Canada. Methods: We used fire history data, satellite and air photo images, and field sampling to determine fire history and severity, and subsequent effects on tree and lichen species composition, in a 880, 000 ha study area in the winter range of the Bathurst caribou herd. Results: We found that low‐ and mixed‐severity fires were more common than high‐severity fires, and that forest fire severity increased with distance to treeline. Forest structure and composition were more important drivers of lichen cover than fire severity or time since fire. Conclusions: While fire had a dominant role in forest structure and composition, the effects on lichen availability were due more to variation in tree growth. We found little evidence of changes in fire regime over the length of our reconstructions (approximately 200 years); however, increases in temperature and the positive relationship between temperature and fire frequency may lead to shortened fire cycles causing a reduction in the availability of forage lichens through burning. Abstract : In our study of fire and lichen dynamics, we found that low‐ and mixed‐severity fires were more common than high‐severity fires, and forest attributes were more important drivers of lichen cover than fire parameters. Fire had a dominant role in forest structure and composition, but the availability of lichens for barren‐ground caribou was mostly due to variation in tree growth.